A case of Cheilognathopalatoschisis in a simmental breed calf: A rare case - Durmus, Ali Said; Polat, Eren (Ankara Univ Press, 2022)
The subject of this study was a 7-day-old female Simmental calf brought to Firat University Veterinary Faculty Animal Hospital Surgery Clinic with the complaint of cleft in the upper lip and palate. In the clinical examination, it was determined that the calf had respiratory difficulties and the nostrils were not formed normally. The calf was diagnosed with cheilognathopalatoschisis. Palatoplasty and reconstructive surgery were performed on the calf for the treatment of the rarely encountered case. The mucosa of the cleft hard palate was freed by dissecting from the os palatinum on both sides. Then, the hard palate was repaired by suturing the mucosal edges mutually. Palatal and alveolar clefts were repaired using Veau's technique. During the post-operative interview with the patient's owner, it was learned that the calf had difficulty in swallowing during feeding. It was determined that the calf died on the 8th postoperative day due to aspiration pneumonia that developed due to the absence of probable swallowing reflex.
Simental ırkı bir buzağıda Şilognatopalatoşizi olgusu: Nadir bir olgu
Keywords: Anomaly; calf; cheilognathopalatoschisis; congenital; simmental